A Clinical Study to Evaluate the Efficacy of Ashmarihar Kwatha with Pashanbhedadi Kwatha in the Management of Mootrashmari (∼Urolithiasis)- Open-Labelled Randomized Comparative Clinical Trial - Komang Sudarmi; T. S. Dudhamal; Manisha Mansukh Kapadiya (Indian Journal of Health Sciences and Biomedical Research KLEU, 2026)
Background: Urolithiasis, the formation of urinary stones, is a prevalent global health issue. It commonly causes severe acute back pain and can lead to serious complications such as pyelonephritis or acute renal failure. Kidney stone formation is a common urological problem with a lifetime prevalence of approximately 10% in men and 6% in women. The study aimed to evaluate and compare the clinical effect of Ashmarihar kwatha (AK) and Pashanbhedadi kwatha (PK) in the management of Mootrashmari (∼Urolithiasis).Material and Method: The primary objective of the study was to assess the clinical efficacy of Ashmarihar kwatha and Pashanbhedadi kwatha in the management of Mootrashmari (urolithiasis) based on symptomatic and stone-related parameters, while the secondary objective was to evaluate the safety and additional therapeutic effects of the interventions through laboratory investigations and ultrasonographic findings. This was an open-labelled randomized comparative clinical trial. A total of 135 cases were screened, and 82 patients diagnosed with Mootrashmari satisfying the study criteria were enrolled. 53 cases were excluded. Participants were randomly assigned to group AK (n=32 completed) and group PK (n=39 completed). Both Kwathas (coarse powder, 10 gm) were administered orally as an internal medication twice a day before food for 60 days.Result: Both groups showed similar statistical effects across all parameters. However, a statistically highly significant result was obtained in the expulsion of the number of stones in the AK group while PK group showed non-significant improvement within groups.Conclusion: Ashmarihar kwatha and Pashanbhedadi kwatha both the show statistically similar efficacy between the group in the management of Mootrashmari (∼Urolithiasis).